2005
DOI: 10.1089/ten.2005.11.626
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Organoid Formation in Collagen Sponge of Cells Isolated from Human Liver Tissues

Abstract: We examined whether small hepatocytes (SHs), which are hepatic progenitor cells, could be isolated from a normal human liver and whether human hepatic cells could form hepatic organoids in a collagen sponge. Normal liver tissues were obtained from resected specimens from nine patients who underwent hepatic resection. Isolated hepatic cells were plated on dishes and a collagen sponge. More than 1 month later, SH-like cells appeared and proliferated on the dishes, whereas cell aggregates were formed in the spong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 22 publications
(23 reference statements)
0
8
0
Order By: Relevance
“…Compared to the use of mature parenchymal cells that are terminally differentiated, hepatoblast‐like hepatic progenitor cells have the potential to divide and differentiate, and may self‐organize better into a 3D liver‐like tissue. In one of the first studies of hHOs, donor (adult) human small hepatocytes (SHs) and non‐parenchymal liver cells, cultured in an organoid format within collagen sponges processed from bovine tendon, produced functional hepatocyte‐like cells that were spatially segregated to the outer layer, some biliary duct formation, and surrounding vascular structures (Sugimoto et al ., 2005). This study demonstrates several principles of organoids, including the use of progenitors, spatial segregation and aggregation, morphogenesis, and differentiation.…”
Section: Hepatic Biliary and Pancreatic Organoidsmentioning
confidence: 99%
“…Compared to the use of mature parenchymal cells that are terminally differentiated, hepatoblast‐like hepatic progenitor cells have the potential to divide and differentiate, and may self‐organize better into a 3D liver‐like tissue. In one of the first studies of hHOs, donor (adult) human small hepatocytes (SHs) and non‐parenchymal liver cells, cultured in an organoid format within collagen sponges processed from bovine tendon, produced functional hepatocyte‐like cells that were spatially segregated to the outer layer, some biliary duct formation, and surrounding vascular structures (Sugimoto et al ., 2005). This study demonstrates several principles of organoids, including the use of progenitors, spatial segregation and aggregation, morphogenesis, and differentiation.…”
Section: Hepatic Biliary and Pancreatic Organoidsmentioning
confidence: 99%
“…polylactic acid, polyglycolic acid, and polyethylene glycol hydrogels) [810] and natural (e.g. collagen, alginate and chitosan) [1114] three-dimensional (3D) scaffolds that provide an environment supporting the maintenance and growth of hepatocytes. More recently, studies have shown that organ decellularization is an attractive strategy because it allows the creation of a naturally occurring 3D biomimetic scaffold that is available for tissue engineering [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…There are currently two main approaches for generating physiologically relevant liver organoids: sandwich cultures and self-assembling spheroids 28, 31 . In sandwich culture models, patient-derived hepatocyte progenitor cells are seeded between layers of collagen or Matrigel in order to replicate in vivo liver morphology and maintain epithelial hepatocyte polarity 28 .…”
Section: Tissue Specific Organoid Models For Translational Medicinementioning
confidence: 99%
“…In sandwich culture models, patient-derived hepatocyte progenitor cells are seeded between layers of collagen or Matrigel in order to replicate in vivo liver morphology and maintain epithelial hepatocyte polarity 28 . In contrast, self-assembling spheroids are formed when hepatocyte progenitor cells are cultured alongside stromal cells in a collagen sponge 31, 32 . Spheroids such as these more closely resemble in vivo hepatocyte physiology with cells forming better tight junctions, cell polarity, protein expression and metabolic activity.…”
Section: Tissue Specific Organoid Models For Translational Medicinementioning
confidence: 99%